Homologous Recombination and Human Health: The Roles of BRCA1, BRCA2, and Associated Proteins - Prakash, Rohit (Cold Spring Harb Perspect Biol, 2015)
Homologous recombination (HR) is a major pathway for the repair of DNA double-strand breaks in mammalian cells, the defining step of which is homologous strand exchange directed by the RAD51 protein. The physiological importance of HR is underscored by the observation of genomic instability in HR-deficient cells and, importantly, the association of cancer predisposition and developmental defects with mutations in HR genes. The tumor suppressors BRCA1 and BRCA2, key players at different stages of HR, are frequently mutated in familial breast and ovarian cancers. Other HR proteins, including PALB2 and RAD51 paralogs, have also been identified as tumor suppressors. This review summarizes recent findings on BRCA1, BRCA2, and associated proteins involved in human disease with an emphasis on their molecular roles and interactions.